2013
DOI: 10.1039/c3sc21931c
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and enhanced conductivity of an IT-SOFC cathode based on a complex perovskite superstructure with six distinct cation sites

Abstract: Epitaxial thin films of the 10 layer cubic perovskite superstructure Ba 1.7 Ca 2.4 Y 0.9 Fe 5 O 13 were grown by pulsed laser deposition, retaining the six distinct cation sites found in the bulk material. Growth on single crystal strontium titanate (STO) (0 0 1) substrates changes the observed symmetry from orthorhombic to tetragonal and orients the layer stacking direction of the superstructure normal to the substrate plane. The material is a candidate cathode for solid oxide fuel cells (SOFCs) and in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Lowering the operating temperature of SOFCs to an intermediate temperature range of 600 • C -800 • C is an ongoing area of intense research and many materials have been suggested as suitable electrolytes 1-3 and electrodes [4][5][6][7][8][9] for this purpose. Popular and promising alternatives are fuel cells, and a substantial amount of research and development has been undertaken to improve the materials used in, and the design of, these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the operating temperature of SOFCs to an intermediate temperature range of 600 • C -800 • C is an ongoing area of intense research and many materials have been suggested as suitable electrolytes 1-3 and electrodes [4][5][6][7][8][9] for this purpose. Popular and promising alternatives are fuel cells, and a substantial amount of research and development has been undertaken to improve the materials used in, and the design of, these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the total conductivity of the film substantially decreases with increases in grain boundary area due to the depletion of oxygen vacancy by the negative space-charge layer enriched through trivalent dopant (Sm 3+ ) in cerium oxide 70 . In this regard, the increase in the preferential orientation of film will enhance the overall ionic conductivity by reducing the grain boundary resistance 71 . Similar behavior was observed in the various literature reported for the trivalent doped cerium oxide thin film 64, 72 .
Figure 14Arrhenius plot for a thin film with respect to the substrate temperature.
…”
Section: Resultsmentioning
confidence: 99%
“…[52][53][54] Combining this with technological breakthroughs in thin film and solid state synthesis procedures allow for the fabrication of "designer" layered compounds and thus greater control is achievable allowing previously unobtainable metastable or hard-to-synthesise layered compounds to be realised. [55][56][57][58] In this work, using cation substitution in the oxide layer we computationally predict…”
Section: Electrons Neighbouring Eachmentioning
confidence: 99%